The Influence Of Management Accounting's Role In Improving The Competitiveness Of Msmes In The Digital Era - Maulana Akmal Malik; Fredy Olimsar; Yuliusman; Wirmie Eka Putri (Citakonsultindo, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in supporting national economic growth, employment absorption, and improving public welfare. The rapid development of digital technology has led to increasingly competitive business competition, requiring MSMEs to adapt to changes in the business environment. One factor that can help MSMEs improve their competitiveness is the implementation of management accounting supported by digital technology. This study aims to analyze the influence of management accounting on the competitiveness of MSMEs in the digital era among MSMEs in Jambi City, Indonesia. The study used a cross-sectional survey design with a purposive sampling technique. A total of 80 respondents were involved in this study. Data were collected using a validated questionnaire and analyzed using multiple linear regression analysis with the help of IBM SPSS version 26. The results showed that management accounting has a positive and significant effect on the competitiveness of MSMEs, R² = 0.672, F = 32.765, p < 0.001. Furthermore, digital technology also significantly impacts the competitiveness of MSMEs (β = 0.321, p < 0.001). The study concluded that the implementation of management accounting and the utilization of digital technology can improve operational efficiency, decision-making quality, and the competitiveness of MSMEs in the digital era. The study recommends that MSMEs increase the implementation of digital-based financial recording systems to enhance business sustainability and competitiveness.